Brash syndrome – a rare cause of bradycardia with renal failure - Seng Yung Liew; Yoon Chin Yap; Zhen Zhen Lo (Penerbit UM, 2025)
The BRASH syndrome is a rare clinical pentad characterised by bradycardia, renal failure, atrioventricular (AV) blockade, shock and hyperkalaemia. Patients with BRASH syndrome typically present with bradycardia and hypotension due to the synergistic effect of AV node blocker and hyperkalaemia, compounded by underlying renal failure. In this report, we present a young patient with a history of chronic kidney disease and hypertension, who was taking regular beta-blockers and calcium channel blockers, and presented with persistent dizziness, headache and lethargy, which progressed into bradycardia and shock. These symptoms were refractory to initial resuscitation, requiring inotropic support and urgent haemodialysis. The patient was discharged in good condition after initiating regular dialysis. A high index of suspicion and early recognition are key to managing BRASH syndrome. Standard advanced cardiac life support algorithms without calcium are generally impractical for BRASH syndrome. The prognosis for BRASH syndrome is excellent with timely recognition and management.